Pengaruh Faktor Psikologis terhadap Penggunaan E-SPT dan Dampaknya terhadap Kepatuhan Wajib Pajak - Amir Hidayatulloh; Rizqa Awalia Rahman; Agung Dwi Nugroho; Faishal Prahatma Ganinda; Kahfi Fikrianoor (ITB AAS INDONESIA, 2021)
This type of research is a causal hypothesis testing research. The approach taken in this studies a quantitative approach. This research objective are (1) to find out psychological factors that influence to uses e-SPT, and (2) to find out the use of e-SPT toward personal taxpayer compliance. The population in this research were taxpayer in Indonesia. The sample in research were personal taxpayer in Indonesia. The sampling technique in this research used purposive sampling, with the criteria of taxpayer who have a tax identification number (NPWP) and use of e-SPT. This research obtained 110 respondents. Testing the hypothesis in the study using WarpPLS. This research found that the use of e-SPT by taxpayer influenced by performance expectations, effort expectation, social influence, and facilitating condition. The research also found that the use of e-SPT affected tax compliance.